2006
DOI: 10.1016/s1808-8694(15)30971-x
|View full text |Cite
|
Sign up to set email alerts
|

CT-Scan sheep and human inner ear morphometric comparison

Abstract: The results of this morphometric study of sheep ear are an important contribution to the development of an animal model to be used for surgical training and experimental otologic surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 4 publications
0
30
0
4
Order By: Relevance
“…2 and are taken from Purcell et al (2003) and Seibel et al (2006). The middle ear impedance, ZME, is the impedance seen from inside the inner ear at the OW.…”
Section: Contribution From the Inner Earmentioning
confidence: 99%
“…2 and are taken from Purcell et al (2003) and Seibel et al (2006). The middle ear impedance, ZME, is the impedance seen from inside the inner ear at the OW.…”
Section: Contribution From the Inner Earmentioning
confidence: 99%
“…In humans these two anatomical structures can be found on one identical plane only separated by the linea temporalis. A fact that has not been described by other authors before, presumably because they used complete heads in a CT-scan 7 or focused especially to the middle ear. Another special formation is the big bullous hypotympanon.…”
Section: Outer Morphologymentioning
confidence: 95%
“…Most sizes are smaller, which is a challenge for trainees. As a lot of morphology is similar, these bones might be used for teaching anatomy and surgical techniques as others described before 2,5,7 . The most common alternative to human temporal bones are virtual trainers based on CT-scans of human temporal bones 9,10 .…”
Section: General Viewmentioning
confidence: 99%
“…Borin et al reported that the marmoset monkey model they investigated was appropriate for use in research on primates, whereas Gurr et al (2010) reported that temporal bone dissections in pig cadavers were very helpful in otosurgical education and training. Seibel et al (2006a) aimed to develop a model from anatomical samples obtained from sheep for use in otology training and experimental surgery, and underlined the necessity for alternative and creative models that would enable surgeons to improve their operative skills. Bovine fetuses are considered to be advantageous in that they are a low-cost slaughterhouse material, easy to both obtain and manipulate.…”
Section: Anatomy and Arterial Supply Of Ear In Fetusesmentioning
confidence: 99%
“…Some of the studies regarding ear morphology of animals were carried out to reveal functional roles of ear especially in fossorial rodents (Lange et al, 2004;Lange and Burda, 2005;Mason, 2006), and some other studies (Pracy et al, 1998;Seibel et al, 2006a;Borin et al, 2008) made morphological comparisons to humans. To understand the anatomic problems and vascular diseases, certain techniques like radiography, ultrasonography, computed tomography, and magnetic resonance were applied to animals as well, and carnivores (e.g., cats, dogs) were frequently used for this purpose (Allgoewer et al, 2000;Russo et al, 2002;Eom et al, 2008).…”
mentioning
confidence: 99%